The diameter of sinotubular junction to body surface area is independently associated with incident acute type a aortic dissection - Wuwei Wang; Yiming Liu; Xiaodi Wang; Hong Ran; Fuhua Huang; Jifang Zhou; Xin Chen; Cunhua Su (Journal of Cardiothoracic Surgery)
Abstract Objective The main aim of this study is to measure and calculate the ratio of sinotubular junction diameter to body surface area (RDA) in patients with acute type A aortic dissection (ATAAD) and normal subjects, and to analyze the relationship between RDA and ATAAD to provide guidance for primary prevention of ATAAD. Methods This retrospective observational study totally admitted consecutive 320 patients with acute type A aortic dissection diagnosed in Nanjing First Hospital from March 2017 to March 2021. Meanwhile, 608 healthy subjects who took echocardiography examination in outpatient was selected as controls. The diameter of sinotubular junction (D.STJ) was measured using echocardiography and direct vision (in some ATAAD patients). The differences in body surface area (BSA), D.STJ and RDA index in both groups were assessed. The association between D.STJ and demographic characteristics were established. RDA index was used to distinguish the ATAAD and healthy subjects. Results The diameter of STJ (24.41 ± 2.16 mm versus 26.66 ± 2.60 mm) and RDA index (13.16 ± 1.67 versus 15.40 ± 1.59) were significantly different between dissection group and control group. The D.STJ were found a positive, linear correlation to BSA in the healthy subjects. Multivariate logistic regression showed that RDA index was one of the independent risk factors to associated with ATAAD as a continuous variable (odds ratio (OR), 0.403, 95% confidence interval (CI): 0.352–0.457, P < 0.001) or a categorical variable (RDA cut-off: 13.88 mm/m2, OR, 0.070, 95%CI: 0.050–0.098, P < 0.001). Conclusions RDA index is an independent and key risk factor for ATAAD occurrence. Timely identification of high-risk patients using RDA index has the potential to become an optional guidance for primary prevention of ATAAD.